Functional range of motion for basic seated activities of daily living tasks - Inagaki, Yuji; Ishida, Tomoya; Sugimori, Hiroyuki; Yoshimura, Takaaki; Watanabe, Akihiro; Naito, Yumene; Sawamura, Daisuke (Frontiers in Sports and Active Living, 2025)
IntroductionEfficient performance of activities of daily living (ADLs) requires coordinated movement across multiple upper-limb joints. However, current assessments of joint range of motion (ROM) during ADLs often rely on subjective evaluation and lack precise quantitative data. The functional ROM required for upper-limb movements in a seated position remains unclear, despite its clinical relevance for older adults and individuals with mobility limitations who frequently perform ADLs while seated. Additionally, little is known about how joint-motion requirements differ across similar ADL tasks, such as eating with a spoon versus chopsticks or washing the top versus the back of the head. To address these issues, we aimed to establish standardized ROM values for common upper-limb–related ADLs using three-dimensional motion analysis to enhance rehabilitation goal setting.MethodsThirty-one healthy adults (14 women; mean age 22.9 ± 1.9 years) completed six seated ADLs—face washing; hair washing (top, back); chopstick or spoon eating; bottled-water drinking. Marker-based motion capture (International society of biomechanics guidelines) recorded kinematics. Descriptive statistics and paired t-tests (p < 0.05) assessed task differences.ResultsSignificant differences in upper limb and neck joint angles were observed across ADL tasks. Shoulder elevation was highest during back hair washing (105.0° ± 14.6°) and lowest when eating with chopsticks (39.2° ± 10.9°). Elbow flexion peaked during face washing (122.3° ± 5.2°) and back hair washing (127.9° ± 5.7°), reflecting the need for close hand-to-face contact. Wrist extension was greatest during face washing (−28.7° ± 8.5°), while a significant difference was found between chopstick (−13.7° ± 12.5°) and spoon use (−5.6° ± 5.3°, p = 0.005), indicating task-specific hand control demands. Neck flexion also varied significantly between hair washing conditions (back > top, p < 0.001). Furthermore, when eating with a bowl rather than with a plate, participants showed significantly greater shoulder elevation, elbow flexion, and forearm rotation (p < 0.01), suggesting increased ROM demands shaped by Japanese eating customs.DiscussionThese reference ROMs offer objective targets for seated-ADL rehabilitation and assistive-device design. validation in older adults and clinical populations is warranted to confirm applicability and guide goal setting.